2023
DOI: 10.1002/tox.23965
|View full text |Cite
|
Sign up to set email alerts
|

Family with sequence similarity 111 member B contributes to tumor growth and metastasis by mediating cell proliferation, invasion, and EMT via transforming acidic coiled‐coil protein 3/PI3K/AKT signaling pathway in hepatocellular carcinoma

Yaobo Yang,
Zhaoyong Yan,
Yang Jiao
et al.

Abstract: As a complex systemic disease, primary liver cancer ranks third in death rate for solid tumors worldwide. Family with sequence similarity 111 member B (FAM111B), which was found to be aberrantly mutated in multiple cancers, is a candidate oncogene. We aimed to determine the function and mechanism of FAM111B in hepatocellular carcinoma (HCC). The expression of FAM111B was evaluated in HCC tissues, adjacent tissues, HCC cell lines. The impact of FAM111B on proliferation, invasion, apoptosis and EMT of HCC cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Moreover, the heightened expression of FAM111B in cancer could potentially impact the dynamics of spindle microtubules, a crucial component in cell division. This observation was also supported by another study that showed that FAM111B contributes to tumor growth and metastasis through interaction with the transforming acidic coiled-coil protein 3 (TCC3), which, in turn, activates the PI3/AKT pathway in hepatocellular carcinoma [51]. An essential role of TCC3 is maintaining the spindle and centrosome localization through phosphorylation by Aurora A kinase in mitosis [52].…”
Section: Fam111b and Cancer Progressionmentioning
confidence: 61%
“…Moreover, the heightened expression of FAM111B in cancer could potentially impact the dynamics of spindle microtubules, a crucial component in cell division. This observation was also supported by another study that showed that FAM111B contributes to tumor growth and metastasis through interaction with the transforming acidic coiled-coil protein 3 (TCC3), which, in turn, activates the PI3/AKT pathway in hepatocellular carcinoma [51]. An essential role of TCC3 is maintaining the spindle and centrosome localization through phosphorylation by Aurora A kinase in mitosis [52].…”
Section: Fam111b and Cancer Progressionmentioning
confidence: 61%